A new deep-water goatfish of the genus Upeneus (Mullidae) from Vanuatu, South Pacific - Uiblein, Franz; Causse, Romain (Zootaxa, 2013)
A new goatfish, Upeneus vanuatu (Mullidae), is described based on five specimens collected off two islands of Vanuatu (South Pacific), at depths of 191–321 m, and compared with five closely related species: Upeneus davidaromi (Red Sea), U. mascareinsis (Western Indian Ocean), U. stenopsis (northern Australia, Philippines, 127–275 m), and the more shal-low-occurring Indo-West Pacific species U. subvittatus (26–120 m) and U. vittatus (<100 m). The new species can be dis-tinguished from all other congeneric species by the combination of four characters: number of gill rakers on lower limb, caudal-peduncle depth, interorbital length, and interdorsal distance. Strong allometric variation in body form between the holotype and the four smaller paratypes was found. Based on the lack of lateral body stripes, a rather narrow caudal pe-duncle depth, and large eyes in adults as common characteristics for U. subvittatus and the four deep-water Upeneus spe-cies, the so-called “stenopsis” species group can be distinguished from four other species groups that were established in earlier studies in order to facilitate intrageneric comparisons. The ecological and evolutionary significance of deep-water goatfishes is briefly discussed.